Constructing Multiple Heterostructures on Nickel Oxide Using Rare-earth Oxide and Nickel as Efficient Bifunctional Electrocatalysts for Overall Water Splitting - Sha, Wenbo; Song, Yanhui; Liu, Peizhi; Wang, Jingkun; Xu, Bingshe; Feng, Xinliang; Guo, Junjie (ChemCatChem, 2022)
Constructing heterostructured electrocatalyst is a promising strategy to explore inexpensive and effective catalysts towards oxygen evolution reaction (OER), hydrogen evolution reaction (HER) and the overall water splitting (OWS). Here, amorphous NiO 2D layers decorated with Ni and rare earth oxide (REOx) nanoparticles, which possess multiple heterostructures (Ni−NiO and REOx-NiO), have been synthesized by the sequential electrodeposition on carbon cloth. The electrocatalytic performances for the prepared Er2O3/Ni−NiO and CeO2/Ni−NiO have been evaluated, exhibiting improved HER (39 mV@10 mA cm−2) and OER (318 mV@50 mA cm−2) activities in contrast to the single component, respectively. Additionally, the two-electrode system (Er2O3/Ni−NiO//CeO2/Ni−NiO) presents an excellent OWS property which displays a low potential of 1.58 V to reach 10 mA cm−2. This work helps to deepen the understanding of the synergetic interaction between dissimilar materials in heterostructured catalyst, and provides guidance for the further exploration and evolution of nanomaterials in green energy conversion technology.
CRIS-Team Scopus Importer:2023-03-20
Keywords: amorphous; heterostructures; overall water splitting; sequential electrodeposition